The Assessment of Occupational Safety and Health Risk Management on Construction Projects During the Covid-19 Pandemic - Lendra Lendra; Apria Brita Pandohop Gawei; Lelo Sintani; Delia Monica Afanda; Jermias Tjakra (International Journal of Disaster Management, 2023)
The Covid-19 pandemic has weakened various business sectors, including the construction services business. This research aims to identify OHS risks in building construction projects during the Covid-19 pandemic, provide an assessment and provide control solutions for these risks. The research method begins with identifying risk factors and distributing risk assessment questionnaires to thirty building construction companies. Then determine the risk rating with the Relative Importance Index (RII) and the risk category using the AS/NZS 4360:2004 standard. The risk control questionnaire was finally distributed to three selected respondents, including a director, a project manager, and an OHS manager, all of whom have at least an undergraduate degree. Based on the analysis, it is found that there is a similarity in the ranking of risk factors from the calculation of the RII value and the AS/NZS 4360:2004 standard, indicating that there is a positive and significant relationship between these two methods. The top three risk factors based on RII are: Covid-19 spread, falling from a height, and being electrocuted. Based on the AS/NZS 4360:2004 standard, these three factors are considered high and moderate risk, while the risk control solutions are: comply with and implement health protocols, use PPE, strong/sturdy scaffolding, install safety nets, arranging safe electrical lines, conduct socialization, and educate workers about Covid-19.